2016
DOI: 10.1186/s13068-016-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation and etherification of alkaline lignin to prepare water-soluble derivatives and its performance in improvement of enzymatic hydrolysis efficiency

Abstract: BackgroundDue to the depletion of fossil resources and their environmental impact, woody biomass has received much attention as an alternative resource. Lignin, as the third most abundant biopolymer from biomass, is now considered as an excellent alternative feedstock for chemicals and materials. The conversion of lignin to the value-added products is a key process to achieve an integrated biorefinery of woody biomass. Among these value-added products, lignin-based derivatives with good surface activity can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 57 publications
5
15
0
Order By: Relevance
“…In the first step, DETA‐terminated amide chains were branched on the lignin by reacting sebacic acid and lignin with DETA. The fourier transform infrared (FTIR) and X‐ray photoelectron spectroscopy (XPS) spectra of lignin in Figures S1 and S2 in the Supporting Information exhibit that lignin has carboxyl and hydroxyl groups, which agrees with previous report . The carboxyl groups of lignin can react with amine groups of DETA to form amide, which has been confirmed by XPS spectra in Figure S2 in the Supporting Information.…”
Section: Introductionsupporting
confidence: 90%
“…In the first step, DETA‐terminated amide chains were branched on the lignin by reacting sebacic acid and lignin with DETA. The fourier transform infrared (FTIR) and X‐ray photoelectron spectroscopy (XPS) spectra of lignin in Figures S1 and S2 in the Supporting Information exhibit that lignin has carboxyl and hydroxyl groups, which agrees with previous report . The carboxyl groups of lignin can react with amine groups of DETA to form amide, which has been confirmed by XPS spectra in Figure S2 in the Supporting Information.…”
Section: Introductionsupporting
confidence: 90%
“…Lignin can be incorporated into epoxy resin via three different methods: 1) blending with petroleum‐based epoxy resin, [24,25] 2) modification of lignin followed by epoxidation, [23,26–30] and 3) epoxidation of unmodified lignin [16,31,32] . Although many studies have focused on utilizing lignin in epoxy resin, [23,27,33,34] they mostly used modified lignin (fractionated or lignin monomers) [23,27,29] . For instance, several studies used small compounds obtained from lignin, including syringaresinol, [35] isosorbide diferulate, [36,37] bisguaiacol, [22] diphenolic acid, [38] and ferulic acid [39–41] to synthesize epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature sulfonation, sulfomethylation, oxidation sulfonation, oxidation nitration (Huang et al 2018;Konduri and Fatehi, 2018) Amphoteric surfactant Amination of lignosulfonate (Cai et al 2017;Lou et al 2019;Tian et al 2014) Nonionic surfactant Hydroxyl ammonium reaction, etherification, epoxidation (Chen et al 2016;Huang et al 2019) Fig. 3.…”
Section: Classification Of Lignin Bio-surfactantmentioning
confidence: 99%
“…It was applied in the enzymatic hydrolysis of hardwood bleached pulp, and the result showed an increased glucose yield rate of as much as 18%. Moreover, observation of the fermentation experiment showed that the product was not toxic for fermentation yeast (Chen et al 2016). Cai et al (2017) synthesized lignin amphoteric surfactant (SLQA) by reacting lignin lignosulfonate with (3-Chloro-2-hydroxypropyl)trimethylammonium Chloride (CHPTAC).…”
Section: Chemical Reaction To Produce Lignin-based Bio-surfactantmentioning
confidence: 99%